2014
DOI: 10.15252/embj.201387549
|View full text |Cite
|
Sign up to set email alerts
|

The SNARE protein vti1a functions in dense‐core vesicle biogenesis

Abstract: The SNARE protein vti1a is proposed to drive fusion of intracellular organelles, but recent data also implicated vti1a in exocytosis. Here we show that vti1a is absent from mature secretory vesicles in adrenal chromaffin cells, but localizes to a compartment near the trans-Golgi network, partially overlapping with syntaxin-6. Exocytosis is impaired in vti1a null cells, partly due to fewer Ca(2+)-channels at the plasma membrane, partly due to fewer vesicles of reduced size and synaptobrevin-2 content. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 64 publications
9
38
1
Order By: Relevance
“…3B). Consistent with this, we quantified the intensities of CgA in cytosolic individual granules that are defined as LDCVs (Walter et al, 2014) and showed that the CgA intensity in the LDCV proportion was increased in muted-KD PC12 cells compared with the control cells (Fig. 3C).…”
Section: Morphological Changes Of Ldcvs In Mu Chromaffin Cellssupporting
confidence: 72%
“…3B). Consistent with this, we quantified the intensities of CgA in cytosolic individual granules that are defined as LDCVs (Walter et al, 2014) and showed that the CgA intensity in the LDCV proportion was increased in muted-KD PC12 cells compared with the control cells (Fig. 3C).…”
Section: Morphological Changes Of Ldcvs In Mu Chromaffin Cellssupporting
confidence: 72%
“…Immature DCVs bud off from the trans‐Golgi and undergo several maturation steps, including homotypic fusion with other immature DCVs, vesicle acidification, peptide processing and sorting of cargos . In recent years, a small but growing number of proteins have been identified as playing roles in DCV biogenesis, beginning to shed some light on the molecular mechanisms underlying the steps in DCV maturation . In one approach to identifying proteins important for DCV biogenesis, genetic screens were performed in Caenorhabditis elegans .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In recent years, a small but growing number of proteins have been identified as playing roles in DCV biogenesis, beginning to shed some light on the molecular mechanisms underlying the steps in DCV maturation. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] In one approach to identifying proteins important for DCV biogenesis, genetic screens were performed in Caenorhabditis elegans. [19][20][21][22][23][24][25] These screens identified several molecules important for early stages of DCV biogenesis and maturation, including the small G-protein RAB-2 and several RAB-2 effectors, including the conserved coiled-coil protein CCCP-1.…”
Section: Introductionmentioning
confidence: 99%
“…3d, e, b, f, h, and k). Vti1a is a SNARE that is localized in the TGN and is involved in vesicle generation during exocytosis and the retrograde transport from early and late endosomes to the TGN (Malsam and Sollner, 2011;Walter et al, 2014). Vti1b, another SNARE, is localized in the TGN and late endosomes, and participates in post-Golgi secretory trafficking and fusion of late endosomes (Antonin et al, 2000;Murray et al, 2005).…”
Section: Isolation Of the Fc-fusion Protein From Intracellular Fractionsmentioning
confidence: 99%